Mini aquaculture fish pond design - Hassan, Mohammad Haiqal; Sumin, Viduriati; Jabi, Mohd Azizul Adzman; Mohammad Asyraf1, Mohammad Arman Amerul; Alciey, William Uyo (2022)
Agriculture business activities, including cropping, livestock, and aquaculture can generate substantial profits if well managed. Limited resources, such as land and area available for business use, especially in agriculture and fisheries, pressure the fish farmer to maximize the use of these resources to increase revenues. With the new technology advancement, fish farming in tanks has become more popular and used by the fish farmer. A fish farmer produces fish in confined places to efficiently convert fish food into fish flesh. Fish tanks conserve space and water and, more importantly, can be harvested faster compared to traditional practices. Thus, this study will guide the students to prepare the mini aquaculture fish pond to be applied in actual business activities and to identify the innovation talent among the students in preparing their mini aquaculture fish pond design.